FORMATION OF SPEECH COMPETENCE IN PRESCHOOLERS BASED ON GAME ACTIVITIES - Adkhamjonova Mohlarbonu, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. In this article, the author emphasizes the role and importance of play activities of preschoolers in the formation of speech competence. Pedagogy considers various  possibilities  of  using  play  activities  to  form  various  knowledge,  skills  and abilities in a child, forms of organizing a game in a kindergarten group in order to develop practical recommendations for educators and parents taking into account age characteristics.